Indigenous and Black Confraternities in Colonial Latin America: Negotiating Status through Religious Practices - De Luca, Candela; Dierksmeier, Laura; Farman Sweda, Krystle; Germeten, Nicole von; Graubart, Karen B; Gómez, Ximena; Jaque Hidalgo, Javiera; Jaque Hidalgo, Javiera; Kirstin Koeltzsch, Grit; Maia Borges, Célia; Masferrer León, Cristina Verónica; Mello e Souza, Marina de; et al. (Connected Histories in the Early Modern World, 2022)
Frontmatter -- Connected Histories in the Early Modern World -- Table of Contents -- Introduction -- Part I. Indigenous and Black Confraternities in New Spain -- 1. Religious Autonomy and Local Religion among Indigenous Confraternities in Colonial Mexico, Sixteenth-Seventeenth Centuries -- 2. Confraternities of People of African Descent in Seventeenth-Century Mexico City -- 3. "Of All Type of Calidad or Color" -- Part II. Indigenous and Black Confraternities in Peru -- 4. Confraternal "Collections" -- 5. "Of Greater Dignity than the Negros" -- 6. African-Descent Women and the Limits of Confraternal Devotion in Colonial Lima, Peru -- 7. Glaciers, the Colonial Archive and the Brotherhood of the Lord of Quyllur Rit'i -- Part III. Indigenous Confraternities in the Southern Cone -- 8. Immigrants' Devotions -- 9. The Marian Cult as a Resistance Strategy -- 10. Between Excess and Pleasure -- Part IV. Black Brotherhoods in Brazil -- 11. Black Brotherhoods in Colonial Brazil -- 12. Cultural Resistance and Afro- Catholicism in Colonial Brazil -- 13. "Much to See and Admire" -- Afterword -- Bibliography -- Contributors -- Acknowledgements -- Index